COMMUNITY-BASED TOURISM POTENTIAL DEVELOPMENT STRATEGY IN SELAT VILLAGE, SUKASADA DISTRICT, BULELENG DISTRICT - Putu Agita Hary Devianti; Ida Ayu Tary Puspa; I Made Arsa Wiguna (Ride: Journal of Cultural Tourism and Religious Studies, 2024)
The research aimed to analyse the tourism potential in Selat Village as well as the strategies used to develop the tourism potential. Cooper's tourism destination development theory was used in this study. This research used qualitative and descriptive methodology, and data obtained through interviews, observation and literature study. This study also used qualitative data analysis and SWOT analysis. The results of the research show that the tourism potential of Selat Village is cultural sites in the form of Pura Kahyangan Desa Adat Selat Pandan Banten and Panglukatan Pancuran Dasa Mala; the potential of natural tourism parks, namely the Village Forest, Camping Area, Outbound, Yoga and Meditation Area; rural conditions in the form of Jogging tracks; agricultural/plantation land in the form of Agrotourism/ecotourism; cultural and artistic events consisting of Genggong Art, Genjek Art, Baleganjur/Gong Kebyar, Cultural Festival, and Weaving Tradition. Most of Selat Village's tourism potential has not been managed well, so that local communities have not fully enjoyed its benefits. The results of the SWOT analysis show that there are four alternative strategies namely: SO (Strengths-Opportunities) strategy, ST (Strengths-Threats) strategy, WO (Weaknesses-Opportunities) strategy, and WT (Weaknesses-Threats) strategy.